Gökçeada – a Turkish island on the Thracian Sea - Lorenc, Marek W. (GEOTOURISM (Geoturystyka), 2013)
Thracian Sea about 20 km west of the Gallipoli Peninsula. Archaeological discoveries have so far indicated that colonization on this island dates back to 3000 BC. Currently, about 8300 people live on Gökçeada, including about 250 inhabitants of Greek origin. The diversity of the island’s geological structure affects its rich relief and area colouring. Cliffs on the northern coast and beaches on the southern one, high mountains and deep canyons in the central part of the island attract fans of solitude, diving and nature. Monuments from the time of the Roman Empire are rare on the island. One of them is a huge rock with two tombs hewn out in it. It is located in a completely uninhabited and treeless area. There are seven old plate trees on the island registered as natural monuments. The youngest one is 180 years old and the oldest tree is almost 630 years old.